Nationalism Narrative and The State Policy on Hizbut-Tahrir in Indonesia - Aswar, Hasbi (Nation State: Journal of International Studies, 2022)
After enjoying free and open political conditions for a long time, Hizbut Tahrir Indonesia, a transnational political Islamist movement, had to face the government's coercive response in 2017 when the government decided to disband this movement in consideration of violations of state principles and threatening the Republic of Indonesia. This paper tried to elaborate on the country's stigmatization efforts against HTI to create a negative picture of this group. The concept used is a stigmatization approach in the study of social movements as one of the state's strategies in repressing a movement that is considered threatening. The method used is qualitative, with data taken from books, journals, and online media sources. This article concludes that the Indonesian government has successfully used the stigmatization method to inhibit the influence of HTI in Indonesia. Stigmatization is carried out through various narratives against this movement, especially related to threats to ideology and political traditions in Indonesia.